Analisis Hukum Islam terhadap Tradisi Tajdid Al-Nikah di Desa Kampungbaru Kecamatan Kepung Kabupaten Kediri - Miftahuddin Yusuf Hanafi; Ahmad Hafid Safrudin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
In the practice of munakahat (marriage) is often found the tradition of tajdid al-nikah (renewal of marriage) carried out by some communities which are believed to cause several factors that encourage the perpetrator to do so. The appearance of tajdid al-nikah by them is not separated from the problems that arise in the bonds of the household that they are experiencing, ranging from domestic disharmony, economic factors and sincerity. In this study, researchers discussed the tradition of tajdid al-nikah} that occurs in Kampungbaru Village that is happening. In the process tajdid al-nikah is not much different from the previous marriage agreement, only the difference lies in the woman who is the legal wife of the man of the name. This tradition is triggered by married couples who in wading through the maghligai of their households have a lot of problems. Judging from Islamic law concerning the tradition of tajdid al-nikah that occurs in Kampungbaru Village there is a mistake, the first opinion says it is permissible because in its implementation does not violate the provisions of Islamic law and this is an opinion that sahih. The second opinion says that tajdi'd al-nika'h} is not allowed because it can cause damage to the first contract (fasakh) and this is a weak opinion.